1985
DOI: 10.1007/bf00712241
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spinal cord stimulation upon myosin light chain and tropomyosin subunit expression in a fast muscle (posterior latissimus dorsi) of the chick embryo

Abstract: Latissimus dorsi muscles of the chick consist of a slow (ALD) and a fast (PLD) muscle. The influence of chronic spinal cord stimulation in the chick embryo upon the expression of myosin light chains and tropomyosin subunits was investigated. Early in development the two muscles exhibited the same ratio of alpha- and beta-tropomyosin subunits. Later, in the slow muscle the ratio beta:alpha decreased and in chicken the amounts of the two components were about the same. In the fast muscle, the alpha-subunit incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1986
1986
1997
1997

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Natural recovery for 4 weeks produced similar fibre type proportions to those of the stimulated group. This ability of low-frequency chronic stimulation to accelerate the acquisition of slow myosin has also been demonstrated in developing avian fast muscle (Gardahaut, Rouaud, Renaud & Ledouarin, 1985) and when adult fast muscle regenerates following Marcaine-induced degeneration (Rosenblatt, Kuzon, Houston, McKee & Plyley, 1988).…”
Section: Resultsmentioning
confidence: 95%
“…Natural recovery for 4 weeks produced similar fibre type proportions to those of the stimulated group. This ability of low-frequency chronic stimulation to accelerate the acquisition of slow myosin has also been demonstrated in developing avian fast muscle (Gardahaut, Rouaud, Renaud & Ledouarin, 1985) and when adult fast muscle regenerates following Marcaine-induced degeneration (Rosenblatt, Kuzon, Houston, McKee & Plyley, 1988).…”
Section: Resultsmentioning
confidence: 95%
“…2, lane e), there are six light chains, three of which comigrate with the adult light chains of the fast type (16,000, 18,000 and 25,000) and two comigrate with the slow type 20,000 and 27,000. This pat tern is not an unusual one in embryonic muscle, in which, as many authors have shown [12,13], there are both the fast and slow light chains, and only at the time of birth does the type of innervation determine the terminal differentiation into fast and slow fibers [14], It is interesting that, in our extracts of 13-and 42-stage embryos, traces of another light chain were present, a 15,000 chain. The results reported here suggest that the appearance of myosin light chain is developmentally regulated, changing from a non-muscle to a muscle type during the dif ferentiation of the myotome.…”
Section: Discussionmentioning
confidence: 81%
“…With respect to the peptide map of MHC of each isomyosin, the two isoforms SM, and SM, identified in the embryonic ALD muscle are indistinguishable from those expressed during neonatal and adult stages [19]. However, in terms of MLC composition, embryonic and neonatal myosins are different from adult myosins [9,10,11,21,241. While the early embryonic ALD contains fast MLC in large amounts (40% of the total MLC), fast MLC are progressively replaced by slow MLC, so that in the ALD muscle of 2-day-old chicken fast MLC represent only 8 % of the total MLC [lo].…”
Section: Fast-twitch Pld Musclementioning
confidence: 90%
“…Slow-tonic and fast-twitch muscles in adult chicken contain both slow and fast myosin isoforms, characterized by their mobilities on native gel electrophoresis [I, 151, their light chain subunits [I61 and their heavy chain components [ I , 2,4,18,251. Changes in myosin light chain subunits during muscle development have been extensively studied (9, 10,11,21,24,261. Moreover, in avian fast pectoralis muscle, a developmentally regulated transition involving a heavychain sequential expression has been described [5, 6, 18, 25, 301. * To whom offprint requests should be sent The developmental changes in native myosin isoforms in avian skeletal muscles have been incompletely investigated.…”
Section: Introductionmentioning
confidence: 99%